A cross-sectional study on infectious health risks regarding freshwater sports practice in Brittany, France. (25th January 2022) - Velardo, Fanny; Bouziri, Hanifa; Adélaïde, Lucie; Oliosi, Emma; Layan, Maylis; Descamps, Alexandre; Berthod, Delphine; Patlán-Hernández, Alan R.; Ledrans, Martine; Pivette, Mathilde; Lefort, Mathilde; Roux, Jonathan; et al.
Abstract: Freshwater sports expose practitioners to pathogens in the water environment and may result in infection. In French Brittany, these infections are particularly worrying, especially since 2016 with an increase in the incidence of leptospirosis reaching 1 case per 100, 000 inhabitants, which represents the highest incidence observed since 1920. We aimed to estimate the prevalence of infectious diseases related to freshwater sports practice and to identify the factors associated with these infections among freshwater sports licensees in Brittany, France. From March 18, 2019, to May 8, 2019, we interviewed freshwater sports licensees (online study) and club presidents and instructors (phone study) in Brittany. Licensee participants were 18 years old or more and practiced at least one freshwater sport in one of the 79 Brittany clubs. We used logistic regression models to study the association between our variables of interest and potential risk factors. In total, 551 licensees (20.3% of the total number of licensees) and 38 clubs (48.1%) were surveyed. Among the licensees, 29 (5.3%) reported being diagnosed with leptospirosis, of which 12 (41.3%) occurred in the last 5 years. The most reported symptoms were skin irritation/itchy skin (24.3%) and 39 individuals (7.1%) reported at least one hospitalization in their lifetime for a disease related to freshwater sports. The occurrence of leptospirosis was negatively associated with boarding from a pontoon (odds ratio (OR)=0.20, 95% confidence interval (95% CI) 0.06–0.56), practicing for less than 4 years (OR=0.17, 95% CI 0.04–0.56) compared to more than 10 years, and the occurrence of leptospirosis was positively associated with taking a soapy shower after practice (OR=4.38, 95% CI 1.90–10.51). Eskimo roll was positively associated with the occurrence of otitis and conjunctivitis (OR=3.22, 95% CI 1.82–6.03), and skin irritation/itchy skin (OR=1.66, 95% CI 0.99–2.84). Otitis, conjunctivitis, and skin irritation/itchy skin are the most commonly reported freshwater sport-related diseases in French Brittany. Despite a good level of knowledge of prevention measures, their implementation by licensees and clubs remains low. Further studies are needed to identify practices associated with infectious risk in freshwater sports. HIGHLIGHTS: This study contributes to a better understanding of the burden of infectious diseases linked to the practice of freshwater sports. One of the main results is that despite a good knowledge of prevention measures, their implementation by licensees and clubs practicing freshwater sports remains weak. These observations could help to better define prevention measures to improve the health of practitioners.